Pengaruh Penggunaan Media Video Animasi dalam Meningkatkan Keterampilan Menulis Teks Cerita Pendek pada Siswa Kelas VIII Sekolah Menengah Pertama Islam Terpadu Baitul Qur’an Tahun Pembelajaran 2025–2026 - Widara Triani; Susy Deliani; Wina Wulandari (Universitas Islam Sumatera Utara, 2026)
This study examined the effect of animated video media on improving short story writing skills among eighth-grade students at Baitul Qur’an Integrated Islamic Junior High School, Tanjung Morawa, during the 2025–2026 academic year. The research was motivated by students’ limited ability to develop ideas, organize narrative structures, and express creativity in short story writing. The study addressed whether animated video media significantly influenced students’ writing performance. A quantitative approach employing a quasi-experimental method with a pretest–posttest control group design was implemented. The population consisted of all eighth-grade students, while the sample included an experimental class of 22 students and a control class of 20 students. Data were collected through short story writing tests administered before and after the treatment and analyzed using normality, homogeneity, t-test, and Scheffé test procedures. The findings revealed a substantial improvement in the experimental group after the implementation of animated video media, with the posttest mean score increasing to 87.42 compared to 71.45 in the control group. Statistical analysis demonstrated that the calculated t-value (15.33) exceeded the critical value (2.08), while the Scheffé test confirmed a significant effect with an F-value of 105.11 surpassing the critical value of 4.07. The study concludes that animated video media effectively enhances students’ short story writing skills by stimulating imagination, increasing engagement, and facilitating understanding of narrative structure and intrinsic literary elements.